Soil water holding capacity and its related properties for brackishwater shrimp farming along Dakshina Kannada District, Karnataka, India - Varadaraju, S; Nagaraj, M K; Shashidhar H, Badami (Indian Journal of Fisheries, 2016)
Selection of suitable site for aquaculture plays an important role in the success of shrimp farming since it is helpful in properplanning, designing, construction, operation and maintenance of ponds. Soil samples were collected from different locationsalong Dakshina Kannada District of Karnataka and selected physico-chemical parameters were analysed. The values of soilparameters recorded were: water holding capacity: 28.2 to 59.80%, bulk density: 2.03 - 2.27, pH: 4. 46 - 6.77, salinity:0 - 2.95 ppt, organic matter: 1.53 - 5.95% and permeability: 3.16 x 10-5 - 2.28 x 10-7 cm sec-1. Textural class of the soil variedfrom sandy loam to sandy soil. Correlation analysis showed that the water holding capacity of the soil increased with theincrease of silt, clay, density and organic matter. The water holding capacity decreased as the sand, voids ratio and porosityof the soil increased. The resuls of the present study suggests that the permeability of soils tested lie within the desirablerange and suitable management practices are to be adopted in the case of sandy loam and sandy soil.